A fuzzy expert system for the human reliability analysis of crews in simulated nuclear emergency procedures. (25th January 2010) - Zio, E.; Baraldi, P.; Librizzi, M.
The use of Human Reliability Analysis (HRA) for a particular safety assessment is still a difficult problem. In order to perform a comparison of the available methods, the best approach is simulation. In this regard, the pilot study proposed by the Organisation for Economic Co-operation and Development (OECD) Halden Reactor Project (HRP) is intended to provide a first guidance in HRA methods evaluation through experimental data on crew performance in simulated scenarios. The quantitative evaluation of the results of these simulations in terms of crew performance and Human Error Probabilities (HEPs) is quite a difficult task. In this paper, a fuzzy expert system for systematically assessing crew performance is presented. The feasibility of the method is proved on a case study concerning a scenario of an incomplete scram in a Boiling Water Reactor (BWR).